2012
DOI: 10.1093/geront/gns075
|View full text |Cite
|
Sign up to set email alerts
|

Holding Abusers Accountable: An Elder Abuse Forensic Center Increases Criminal Prosecution of Financial Exploitation

Abstract: Previous studies have not demonstrated that elder abuse interventions impact outcomes; this study breaks new ground by showing that an elder abuse multidisciplinary team increases rates of prosecution for financial exploitation. The elder abuse forensic center model facilitates cooperation and group problem solving among key professionals, including APS, law enforcement, and the DA and provides additional resources such as neuropsychological testing, medical record review, and direct access to the Office of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
35
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 87 publications
(35 citation statements)
references
References 18 publications
0
35
0
Order By: Relevance
“…All of the studies we identified [36][37][38][39][40][41][42][43][44][45] were heterogeneous and had substantial limitations, and it is therefore difficult to recommend any of the studied interventions.…”
Section: What Evidence Supports Interventions To Combat Elder Abuse?mentioning
confidence: 99%
See 1 more Smart Citation
“…All of the studies we identified [36][37][38][39][40][41][42][43][44][45] were heterogeneous and had substantial limitations, and it is therefore difficult to recommend any of the studied interventions.…”
Section: What Evidence Supports Interventions To Combat Elder Abuse?mentioning
confidence: 99%
“…However, there has been only one study demonstrating a statistically significant measurable outcome for a multidisciplinary team. 45 This was a case-control study of the Los Angeles County Elder Abuse Forensic Center (n = 287), which showed increased rates of prosecution for financial abuse with a multidisciplinary team. This study addressed only financial abuse, however, and its results cannot be extrapolated to other types of abuse that may be harder to prove in the justice system.…”
Section: What Evidence Supports Interventions To Combat Elder Abuse?mentioning
confidence: 99%
“…Wiglesworth, Mosqueda, Burnight, Younglove, and Jeske (2006) performed a Level 1 evaluation showing improved attitudes toward the efficiency and effectiveness of an elder abuse forensic center. MDTs modeled after programs in domestic violence interventions appear to be successful in terms of Level 1 satisfaction and attitudes, and Level 3 recognition of abuse, referral to protective services, money management and housing services, review by the District Attorney’s Office, and higher rates of prosecution and conviction (Navarro, Gassoumis, & Wilber, 2013; Rizzo et al, 2015; Teaster, Nerenberg, & Stansbury, 2003). …”
Section: State-of-the-science Related To Abuse Prevention: Applicatiomentioning
confidence: 99%
“…Case studies documented the effectiveness of the forensic teams in submitting their cases to the District Attorney and for prosecution, especially in cases of financial exploitation (Wiglesworth et al 2006). In the second study, Navarro et al (2013) analyzed case reports from the EAFC, finding that the program increased rates of prosecution for financial exploitation by facilitating cooperation and group problem solving among APS, law enforcement, and the District Attorney, in addition to providing additional resources, such as neuropsychological testing and direct access, to the Office of the Public Guardian. Common outcomes included referrals to, and use of, home health services, urgent medication interventions, guardianship, and hospitalization and/or placement.…”
Section: Community Approaches: Case Management/social Service Legalmentioning
confidence: 99%